Creating Meanings and Supportive Networks on the Spiritual Internet Forum "The Nest of Angels" - Marko Uibu (Journal of Ethnology and Folkloristics)
Based on the ethnographic study of Estonian spiritual Internet forum The Nest of Angels, the article observes the process of sharing virtual social support and creating-confirming spiritual meanings. The forum, explicitly opposing the consumeristic side of new spirituality, has become popular and demonstrates the nature and various roles of contemporary spiritual angels. The study identifies two main modes in which the Nest and the presence of angels might be useful for users. Firstly, emotional support is shared, either by fellow users directly or by confirmations that angels will definitely help. Secondly, the Nest allows people to acquire knowledge both on spiritual and practical issues. As the Nest is dialogical, users can pose questions and find confirmations for their otherwise deviant experiences. Discussions in the Nest encourage everybody to interpret some situations and objects (like feathers) as signs from angels. This interpreting process might change people’s perceptions of the world by adding a layer of positive emotions. The study demonstrates how the angelic presence (or at least endeavour towards the presence) helps to establish and keep the tonality of benevolence which functions as the cornerstone of this virtual space. The Nest supports a specific epistemological stance manifested in the angelic, traditional ‘feminine’ values of empathy, softness, and caring. Angels and the idea of angelic presence is the main factor helping to keep the ‘high-vibrational’ and benevolent atmosphere of the forum and empowering the users inside the traditional understanding of ‘feminine softness’.